Hubungan Servant Leadership dengan Kinerja Organisasi pada Perawat Rumah Sakit Dirgahayu Kota Samarinda - Alvenaria, Jane; Prastika, Netty Dyan (Universitas Muhammadiyah Metro, 2025)
The purpose of this study was to determine the relationship between servant leadership and organizational performance. The participants in this study were nurses at Dirgahayu Hospital with a total of 105 subjects. Sampling using simple random sampling. Data collection tools using organizational performance scale and scale development and construct clarification of servant leadership with quantitative methods. Data analysis using correlation test hypothesis technique using SPSS version 26.0 windows program. the results showed that: (1) there is a relationship between servant leadership and organizational performance with the value of F count = 1.822> F table = 3.97 and P value = 0.046. (2) there is a positive correlation between servant leadership and organizational performance with the value of R count 0.305 > R table 0.227 and the value of P = 0.000.